Behavioral intention of using a complementary currency in Palestine - Altarturi, Basheer Hussein Motawe; Othman, Anwar Hasan Abdullah (2020)
The absence of a Palestinian currency deprived the Palestinian Monetary Au-thority of the ability to set its monetary policy, causing a very inflationary system. The primary goal of this study is to undertake an adoption analysis of behavioral intention of using a complementary currency in Palestine. This study adopts the theory of planned behavioral with adding facilitating condi-tion, complexity and trust to the model. To analyze the behavioral intention of using a complementary currency system in Palestine, the study adopts a structural equation modelling. The findings show that attitude, subjective norms, facilitating conditions and trust have a significant positive influence on the behavioral intention. Complexity has a significant negative impact on behavioral intention. Only perceived behavioral control shows an insignifi-cant effect on behavioral intention. This research has expanded the knowledge base of complementary currencies as a tool for monetary sover-eignty. However, the proposed model did not discuss on the mechanism of the system and how it will be implemented technically and legally. Future research is recommended to overtake the technological implementation of the proposed approach and legal issues.